Covalent organic frameworks: efficient, metal-free, heterogeneous organocatalysts for chemical fixation of CO2 under mild conditions - Zhi, Yongfeng; Shao, Pengpeng; Xiao, Feng; Xia, Hong; Zhang, Yumin; Shi, Zhan; Mu, Ying; Liu, Xiaoming (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
The cycloaddition of CO2 to epoxides to form cyclic carbonates is very promising and does not generate any side products. Metal-free, heterogeneous organocatalysts offer an environmentally friendly alternative to traditional metal-based catalysts. Herein two triazine-based covalent organic frameworks (COF-JLU6 and COF-JLU7) were successfully synthesized under solvothermal conditions. The structural and chemical properties of COFs were fully characterized by using powder X-ray diffraction analysis, structural simulation, Fourier transform infrared spectroscopy, 13C solid-state NMR spectroscopy, electron microscopy, thermogravimetric analysis and nitrogen adsorption. The two COF materials combine mesopores, high crystallinity and good stability, as well as a large number of hydroxy groups in the pore walls. They possess a high Brunauer–Emmett–Teller (BET) specific surface area up to 1390 m2 g−1 and a large pore volume of 1.78 cm3 g−1. The COF-JLU7 displays a high CO2 uptake of 151 mg g−1 at 273 K and 1 bar. Importantly, COF-JLU7 was found to be a highly effective catalyst to convert CO2 into cyclic carbonate through the cycloaddition reaction with epoxides under mild conditions. The effect of reaction parameters, such as reaction temperature, reaction time and CO2 pressure, on the catalytic performance was also investigated in detail. Moreover, the new framework-based catalyst can be recovered and reused five times without a significant loss of catalytic efficiency.